Kinetics of Ferrous Sulfate Catalytic Oxidation from Dissolved Iron Waste in Sulfuric Acid - Sulistyo, Hary; Rahayu, Suprihastuti Sri; Sediawan, Wahyudi B; Sarto, Sarto; Syarif, Takdir (ASEAN Journal of Chemical Engineering, 2009)
Iron waste was dissolved in a sulfuric acid to form a concentrated FeSO4- H2SO4 solution This research was conducted by catalytic oxidation of ferrous sulfate using manganese dioxide as catalyst to form a ferric sulfate. Catalytic oxidation reaction using a catalyst of manganese dioxide is a three phase heterogeneous reaction. This reaction kinetics is quite complex. This study aims to develop a mathematical modeling of reaction kinetics for three phases, gas, liquid and solid. Oxidation was undertaken on the condition of isothermal and isobaric in the threeneck flask as reactor. Experiment was run in the temperature range of 313 K to 363 K and catalyst concentration of 4.16 10 -3 gL-1 to 25 10 -3 gL-1. Results indicated that the oxidation rate increased with the increase of temperature and catalyst concentration. Reaction kinetics can be approached with quasi steady state model and chemical reactions on the surface of the catalyst are a step controls the reaction kinetics. The relation between reaction rate constant and temperature in the following Arrhenius form: kR = 2182exp (-17613/RT),L g.eq-1min-1 Manganese dioxide as catalyst can increase a reaction rate and reduce the activated energy which can be expressed in the following equation E = 20129.025exp(-0.0472mk),Jmol-1 Activated energy was found from 14414 Jmol-1to 19747 Jmol-1 and maximum ferrous sulfate conversion was of 97.20%. Those values were similar result with the literature available.